Senior High School Students’ Mathematical Problem Solving Of Three-Variable Linear Equation System - Asok, Abdul Nu'man; Hasanah, A (JTAM (Jurnal Teori dan Aplikasi Matematika), 2021)
The aim of this research is to find the difficulties of students in solving word problems in the three-variable linear equation systems subject. Before they took a mathematical problem-solving exam, the learners were given reinforcement of prerequisite knowledge of the intended subject. The problem-solving test indicators used in this study were taken from Polya's problem-solving steps consisting of (1) recognizing the question, (2) making a plan for problem-solving (developing a plan), (3) implementing the plan for problem-solving, and (4) looking back. The research method used in this study was a qualitative descriptive. The subject in this study was 15 students who were 10 th graders of senior high school. The data were obtained from a student performance who took mathematical problems solving test. The result obtained from this study can be seen from the number of students whose achievement indicators formulate a plan of 49.6%, achievement in completing plans 14.1%, and achievement in checking solutions 2.2%. However, the indicators of understanding the problem area in the good category, namely 80%. The result of this study showed that the students were only able to solve the word problems for understanding the problem (good category) and devising the plan steps (mediocre category), whereas they got difficulties in solving the word problems in carrying out the plan and looking back (low category).